Kemampuan Higher Order Thinking Skill (HOTS) Siswa SMP IT Nurul Islah Banda Aceh Pada Materi Perbandingan - Irma Aryani; Maulida Maulida; Hasanah Hasanah (Jurnal Dedikasi Pendidikan, 2020)
Higher Order Thinking Skills (HOTS) is the ability to parse or develop teaching material, make conclusions, build representations, analyze and relate the information obtained. For example, students understand what they are reading, they will make conclusions and use information obtained in the text they are reading. The 2013 curriculum must integrate HOTS ability in the learning process, namely the ability to think in creating ideas, analyzing, and evaluating. This study aims to determine and analyze the ability of HOTS students in SMP IT Nurul Islah Banda Aceh to solve comparison problems. This type of research is a qualitative descriptive using test and questionnaire instruments. Tests and questionnaires prepared based on HOTS indicators aim to analyze students' HOTS abilities. Then the results of tests, questionnaires, and interviews are combined to be analyzed to get conclusions. Based on research that has been done, it can be concluded that the ability of students to solve mathematical problems HOTS type in the comparison material is a good category, 19 students (57.57%) of 33 students. That is, some students have been able to do the thought process of creating, analyzing, and evaluating in solving problems.